Fault Detection for Wireless Networked Control Systems with Stochastic Switching Topology and Time Delay. (24th June 2014) - Guo, Pengfei; Zhang, Jie; Karimi, Hamid Reza; Liu, Yurong; Wang, Yunji; Bo, Yuming
Abstract : This paper deals with the fault detection problem for a class of discrete-time wireless networked control systems described by switching topology with uncertainties and disturbances. System states of each individual node are affected not only by its own measurements, but also by other nodes' measurements according to a certain network topology. As the topology of system can be switched in a stochastic way, we aim to designH ∞ fault detection observers for nodes in the dynamic time-delay systems. By using the Lyapunov method and stochastic analysis techniques, sufficient conditions are acquired to guarantee the existence of the filters satisfying theH ∞ performance constraint, and observer gains are derived by solving linear matrix inequalities. Finally, an illustrated example is provided to verify the effectiveness of the theoretical results.